Pengaruh Capital Adequacy Ratio, Beban Operasional dan Pendapatan Operasional, Loan To Deposit Ratio, dan Non Performing Loan Terhadap Profitabilitas Perbankan - Dwi Damayanti, Atisyah; Indrabudiman, Amir (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted aiming to determine the Effect of Capital Adequacy Rasio, Operational Expenses and Operational Income, Loan to Deposit Ratio, and Non-Performing Loans on Profitability. This research was conducted on companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) with a research period of 2019 – 2023. The sampling technique in this study used purposive sampling with a sample size of 38 banks that met the criteria. The data analysis used in this study was multiple linear regression analysis using a statistical test tool, namely SPSS version 22.0. The conclusion of the study regarding Operational Expenses and Operational Income, Loan to Deposit Ratio, Non-Performing Loans have a negative and significant influence on profitability, while Capital Adequacy Ratio does not effect on profitability.